Supplements used as hydrating agents in pre- and post-lodging phases to newly-hatched chicks - Pedroso, Adriana Ayres; Stringhini, José Henrique; Leandro, Nadja Susana Mogyca; Café, Marcos Barcellos; Barbosa, Carlos Eduardo; de Lima, Flávia Gontijo (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Two experiments were carried out to evaluate hydrating agents to newly hatched chicks from breeders in early production life. The first experiment studied the effect of commercial hydrating agents in pre-lodging phase in chicks from breeders with 25 weeks of age and submitted to two intervals between hatching and lodging (0 and 48 hours). Agent did not show any favorable effects on dehydration, mortality and performance until 21 days of age. In he second experiment, sodium bicarbonate was used as hydrating agent. The solution was supplied for 24 hours, after 0, 24 and 48 hours intervals between hatching and lodging, to chicks from breeder of 27 weeks of age. The intestinal integrity increased, based on intestinal density and organ weight increment obtained with electrolytes supplementation. As the interval between hatching and lodging increased, the yolk sac decreased. In both experiments, the interval increasing between hatching and lodging promoted higher dehydration and mortality incidence, but performance was better at 21 days of age.